Work Life Quality, Employee Engagement, and Productivity Among Nurses: Insights From A Public Healthcare Organization - Panca Bagja Mohamad; Muhardi; Dede R. Oktini (Kirana Publisher (KNPub), 2026)
Hospitals face increasing pressure to deliver high-quality, safe, and timely healthcare services while managing workforce challenges, including heavy nursing workloads and growing organizational demands. As frontline healthcare providers, nurses play a critical role in ensuring service quality and organizational performance. This study examined the effects of Quality of Work Life (QWL) and employee engagement on nursing productivity at Welas Asih Regional General Hospital, West Java Province, Indonesia. A quantitative cross-sectional survey was conducted among nursing personnel. Data were analyzed using multiple linear regression to assess the partial and simultaneous effects of QWL and employee engagement on productivity. The results showed that both QWL and employee engagement had positive and significant effects on nursing productivity, both individually and jointly. The regression model explained 73.3% of the variance in productivity, indicating a substantial contribution of the two variables. QWL emerged as the more dominant predictor of productivity, suggesting that improvements in working conditions may yield greater productivity gains. Although nurses reported favorable levels of QWL and employee engagement, challenges remained in workload management, work–life balance, and career development. Nursing productivity was generally high, with performance strengths concentrated in service quality rather than work quantity and timeliness. These findings highlight the importance of creating supportive work environments and fostering employee engagement to enhance nursing productivity. Hospital managers should prioritize workforce policies that improve working conditions, strengthen employee involvement, and address workload-related challenges to sustain high-quality healthcare delivery.